2011
DOI: 10.1242/jeb.048884
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between detoxification mechanisms and excretion in Malpighian tubules ofDrosophila melanogaster

Abstract: SUMMARY Insects have long been known to excrete toxins via the Malpighian (renal) tubules. In addition, exposure to natural or synthetic toxins is commonly associated with increases in the activity of detoxification enzymes such as the P450 monoxygenases (P450s) and the glutathione-S-transferases (GSTs). We examined the links between mechanisms for detoxification and excretion in adult Drosophila melanogaster using functional assays and measurements of changes in gene expression by quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 35 publications
1
64
1
1
Order By: Relevance
“…GstD1 encodes a glutathione-Stransferase involved in detoxification metabolism. This gene is regulated when an insect is exposed to a variety of organic compounds (Chahine and O'Donnell 2011). The compared species have different feeding preferences and were fed in different media.…”
Section: Discussionmentioning
confidence: 99%
“…GstD1 encodes a glutathione-Stransferase involved in detoxification metabolism. This gene is regulated when an insect is exposed to a variety of organic compounds (Chahine and O'Donnell 2011). The compared species have different feeding preferences and were fed in different media.…”
Section: Discussionmentioning
confidence: 99%
“…ApGST-E2 was also high in Malpighian tubules, an important physiological (renal) tissue that is vital in eliminating dietary toxins as reported in other insects (Chahine and O'Donnell, 2011). A recent study in D. melanogaster suggested that exposure to toxins evoked a coordinated response by the Malpighian tubules, involving the interaction of detoxification pathways (including GSTs) as well as enhanced excretion (Chahine and O'Donnell, 2011). On the other hand, ApGST-E2 was highly expressed in fat body which is also an important metabolic tissue for detoxification as demonstrated earlier in A. planipennis (Mittapalli et al, 2010) and in the Hessian fly, Mayetiola destructor (Mittapalli et al, 2007).…”
Section: Discussionmentioning
confidence: 59%
“…Several studies of plant-insect interaction have shown the midgut tissue as the major interface for several detoxification enzymes including GSTs (Hakim et al, 2010;Mittapalli et al, 2010;Pauchet et al, 2010;Rajarapu et al, 2011;Zhang et al, 2012). ApGST-E2 was also high in Malpighian tubules, an important physiological (renal) tissue that is vital in eliminating dietary toxins as reported in other insects (Chahine and O'Donnell, 2011). A recent study in D. melanogaster suggested that exposure to toxins evoked a coordinated response by the Malpighian tubules, involving the interaction of detoxification pathways (including GSTs) as well as enhanced excretion (Chahine and O'Donnell, 2011).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In Tenebrio we found expression of cytochrome p450, known for a role in detoxification post-infection (Chahine, 2011;Chung et al, 2011). One sequence in particular, aligned with stress-induced phosphoprotein 1, showed ontologies with various aspects of stress management, development and immune function.…”
Section: Stress-associated Proteinsmentioning
confidence: 93%